Notes on the Etymology of Berber Numerals - Alonso de la Fuente, José Andrés (Anaquel de Estudios Árabes, 2007)
The main goals of this paper are to analyse the etymologies of (Lybian-)Berber numerals recently presented by Václav Blažek and to demonstrate that the relation between the Lybian-Berber and the Semitic languages is not sufficiently self-evident –at least as far as it concerns the original numerical system– even though both are said to be descendants of a common ancestor (namely, proto-Hamito-Semitic).